DEVELOPMENT OF NEUTRALIZING ANTIBODY ASSAYS: PITFALLS AND CHALLENGES - Ahmad, Sharique; Farhana; Agnihotri, Yoshita; Pratap, Pushpendra D; Anwar, Subuhi; Saud, Tuba (International Journal of Research -GRANTHAALAYAH, 2025)
Neutralizing antibody assays are vital in evaluating immune responses to infectious agents and vaccines while assessing the capacity of antibodies to inhibit pathogen infection or replication. These represent a cornerstone for determining vaccine efficacy and therapeutic antibody potential. Yet, a multitude of challenges accompanies the development of reliable and accurate nAb assays. The review deals with nAb testing, uncovering the most frequent pitfalls and challenges in their development, which are classified into the selection of appropriate assay formats, assay protocol standardization, biological variability management, and interpretation of results. Each of the four major assay formats-namely, plaque reduction neutralization tests, microneutralization assays, pseudovirus-based assays, and cell-based assays-offers specific benefits and limitations. Ensuring protocol standardization across laboratories is mandatory to obtain results that are comparable and reproducible. Assay outcomes are substantially affected by biological variability stemming from a host of factors: differing pathogen strains; timing of sample collection. Given the possible options, interpretation of results from nAb tests becomes exceedingly complex due to defining appropriate neutralization thresholds and connecting these to correlates of protection. Addressing some of the aforementioned challenges shall lead to better reliability and reproducibility of nAb assays, propelling the advancement of immunology and infectious disease research. Examples of cases will also be discussed to bolster the argument with warm bodies, such as the fast-track development of nAb assays during the COVID-19 pandemic, while future directions in nAb assays will be outlined, underlining the need for HIV collaborators to outpace demand.